Narratives About Identity Constructions in a Peruvian Nor-Andean Region - Torres Villafane, Jessica Miriam (2023)
This paper aims to discuss the formation of identities in the Ancash region based on a Narrative Inquiry of two families living in the city of Huaraz, the parents are Hirka and Quyllur. Both have faced the same external influences but have opted for different identity constructions. Narrative inquiry employs three dimensions: interaction, continuity, and situation. The data analysis was based on the composition of meanings and the interpretative perspective of the experiences that consist of organizing meanings based on the data and a reflective process by the researcher, and the presentation of the advances to a support group to discuss, review and adjustment of the obtained data. From the analysis of the experiences, we can conclude that Hirka represents cultural resistance and Quyllur cultural assimilation. The first considers that their cultural practices have been inherited from their ancestors; on the other hand, Quyllur does not have this intergenerational awareness.